1988
DOI: 10.1007/bf01713011
|View full text |Cite
|
Sign up to set email alerts
|

Capillary rarefaction characteristic of the skeletal muscle of hypertensive patients

Abstract: There is evidence that the rarefaction of the capillary bed is typical for the skeletal muscle of spontaneously hypertensive rats. We were therefore interested to learn whether there is also a rarefaction in skeletal muscle of human hypertensives. The number of capillaries was morphometrically analysed and counted in the quadriceps and the pectoralis major muscles of human normotensives (n = 12) and hypertensives (n = 15). The clinical diagnosis and certain pathological criteria, such as blood pressure (with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(49 citation statements)
references
References 17 publications
4
44
0
1
Order By: Relevance
“…Previous studies have demonstrated that human essential hypertension is characterized by an increased percentage of fast-twitch muscle fibers 61 -62 and a decreased vascularity of skeletal muscle. 63 In summary, the increased BP response in normotensive blacks appeared to be caused by an elevation in TPR. Blacks did not have increased venous plasma norepinephrine levels, suggesting that other factors (e.g., vascular structure or salt sensitivity) may have contributed to the increased resistance.…”
Section: Mabp=coxtprmentioning
confidence: 85%
“…Previous studies have demonstrated that human essential hypertension is characterized by an increased percentage of fast-twitch muscle fibers 61 -62 and a decreased vascularity of skeletal muscle. 63 In summary, the increased BP response in normotensive blacks appeared to be caused by an elevation in TPR. Blacks did not have increased venous plasma norepinephrine levels, suggesting that other factors (e.g., vascular structure or salt sensitivity) may have contributed to the increased resistance.…”
Section: Mabp=coxtprmentioning
confidence: 85%
“…38 Whether this association is independent of LTPA remains, however, unknown. Furthermore, compared with normotensive subjects, hypertensive subjects have a lower capillary density, 29,39 and the lower the capillary density, the higher the increase in BP from 50 to 70 years of age. 29 Other mechanisms explaining the low peripheral resistance may exist.…”
Section: Discussionmentioning
confidence: 96%
“…These data are seemingly contradictory to those reported by Baron et al [9], who found an inverse correlation between mean arterial blood pressure and leg blood flow using a pharmacological insulin infusion rate of 15 mU/kg × min in normotensive subjects. Whether this defect can be attributed to one or several of the abnormalities found in patients with essential hypertension such as excessive sympathetic activation [60], capillary rarefaction [61] or impaired endothelium-dependent vasodilatation [58,62,63], is currently unclear. Of interest in this respect is the study of Taddei et al [58] who measured both insulin-stimulated glucose uptake and endothelial function in patients with essential hypertension.…”
Section: Defects or Lack Thereof Of Insulin-induced Vasodilatation Imentioning
confidence: 99%